Financial Performance Evaluation - A Comparative Study of Some Selected NBFCs - Paul, Prasanta (Indian Journal of Finance, 2011)
Non-Banking Finance Companies (NBFCs) accomplish various functions and provide a variety of financial services to individuals, businesses and organizational customers. They play an extremely fundamental role in the economic growth of any country. This paper intends to assess, compare, test and analyze the financial performance (FP) of five listed NBFCs as measurement and comparative analysis of financial performance of the companies are intended to assist the finance managers analyse their companies' activities from a financial standpoint and provide useful information needed to take right kind of managerial decisions. Different statistical tools like; Arithmetic Mean, Standard Deviation, Coefficient of Variation, Correlation and Analysis of Variance (ANOVA) have been used extensively to validate the findings of the study. Various kinds of financial ratios have also been used to analyse the financial performance of the selected NBFCs. Two sets of hypotheses have been tested. This paper concludes by saying that the selected companies differ significantly in terms of their financial performance indicators from one to another and there are no significant differences in the last five years in the management of financial performance but the companies have performed well in the last five years.